2015
DOI: 10.18330/jwallacea.2015.vol4iss2pp93-99
|View full text |Cite
|
Sign up to set email alerts
|

Altitudinal Gradient Affects on Trees and Stand Attributes in Mount Ciremai National Park, West Java, Indonesia

Abstract: Understanding the effect of altitude on trees and stand attributes of tropical forests is crucial for the development of effective management and conservation strategies. However, study on this issue in Mount Ciremai National Park is still lacking. A total of 136 plots were set on the eastern slope of Mount Ciremai in Mount Ciremai National Park and investigated in six different altitudes: 500 m a.s.l., 840 m a.s.l., 1,300 m a.s.l., 1,400 m a.s.l., 1,780 m a.s.l., and 2,530 m a.s.l. The objective of this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
2
5
0
Order By: Relevance
“…Conversely, tree size tended to decrease with increasing altitude which is in line with the other studies as reported by Culmsee et al (2010), Reddy et al (2010), and Coomes and Allen (2007). In addition to altitude (Rozak and Gunawan 2015), light competition and nutrient composition influence tree density (Coomes and Allen 2007;Wagner et al 2011). Besides the higher density, the species composition at higher altitudes was also more homogeneous, especially in Plot 3.…”
Section: Good Regeneration Status Of Trees In the Block Of Malagembolsupporting
confidence: 89%
See 1 more Smart Citation
“…Conversely, tree size tended to decrease with increasing altitude which is in line with the other studies as reported by Culmsee et al (2010), Reddy et al (2010), and Coomes and Allen (2007). In addition to altitude (Rozak and Gunawan 2015), light competition and nutrient composition influence tree density (Coomes and Allen 2007;Wagner et al 2011). Besides the higher density, the species composition at higher altitudes was also more homogeneous, especially in Plot 3.…”
Section: Good Regeneration Status Of Trees In the Block Of Malagembolsupporting
confidence: 89%
“…Furthermore, Lithocarpus pallidus, Ficus fistulosa, Phobea grandis, Castanopsis cuspidata, and Trema amboinensis, were reported by Cahyanto et al (2018). Floristic compositions are thought to be related to habitat conditions, soil conditions, topography, distance between locations, altitude, and the number of samples and the sampling techniques used (Coomes and Allen 2007;Baraloto et al 2013;Rozak and Gunawan 2015;Chian et al 2016;Salvana et al 2019).…”
Section: The Dominance Of Fagaceae In the Block Of Malagembolmentioning
confidence: 99%
“…The zonation effect on vegetation in an in situ conservation area has been reported by other studies (Aiba & Kitayama (1999), Fujii et al (2006), Mutaqien et al (2008), Nishimura et al (2006), Rozak and Gunawan (2015), Willinghofer et al (2012)). However, the study on the zonation effects in an ex situ conservation area, particularly in Ir.…”
Section: Introductionsupporting
confidence: 76%
“…Furthermore, ordination method was carried out to confirm the general relationship between the presence of tree species around springs and the environmental factors of species distribution highlighted (elevation, rainfall, and air temperature) by canonical correspondence analysis (TerBraak and Vendonschot 1995; McCune and Grace 2002) using PC-ORD software. Elevation was the factor determining species composition or distribution (Yamada 1990;Siebert 2005;Rozak and Gunawan 2015;Afrianto et al 2017). Rainfall and air temperature were also the important factors for species distribution.…”
Section: Mean Abundancementioning
confidence: 99%